Dynamics of handling time and functional response by larvae of Chrysomya albiceps (Dipt., Calliphoridae) on different prey species - Faria, L. D. B. [UNESP]; Godoy, W. A. C. [UNESP]; Trinca, L. A. [UNESP] (Wiley, 2004)
One way to understand the behavioural patterns exhibited by a predator in response to prey density is to evaluate its functional response. Such evaluation yields information about basic mechanisms of prey-predator dynamics, and is an essential component of prey-predator models. In this paper we analysed experimentally the functional response and the handling time spent by Chrysomya albiceps on different prey species and larval instars of blowflies. The type II functional response was observed when second instar larvae of Chrysomya megacephala and Chrysomya macellaria were consumed. The handling time spent by the predator was significantly different between instars and species. The implications of the functional response and handling time for the interaction dynamics of Brazilian Chrysomyinae species are discussed.
Keywords: Calliphoridae; Chrysomya albiceps; Functional response; Handling time; Larval predation; biological control; functional response; handling time; larva; pest control; predation; Chrysomya; Chrysomya megacephala; Chrysomyinae; Diptera; Megacephala